Mortality after Hip Fractures in Nonagenarians - Kang, Bun Jung (The Korean Society for Bone and Mineral Research, 2012)
OBJECTIVES: Nonagenarians with hip fractures represent a special group of people because of their advanced age and co-morbidities. We evaluated mortality after hip fractures in nonagenarians. METHODS: Fifty-one patients were studied over a 2-year period. There were 39 female and 12 male patients. Twenty seven patients sustained an intertrochanteric fracture of the femur, 24 suffered from femoral neck fracture. The American Society of Anaesthetists (ASA) score of II was the most frequent among 51. Forty-one of them had one or more co-morbidities. Patient review was done 2 years after the fracture. RESULTS: The mortality rate at one year was 53.4% in men, and 15.7% in women. After multivariate analysis, the type of fracture (intertrochanteric fracture) was identified as a risk factor for one-year mortality (P = 0.025). CONCLUSION: The outcome in nonagenarians with hip fractures is poor due to the high rates of mortality, especially in men, and this could be informed to patients and their families before hip fracture surgery.